A Pi-Shaped Slot Antenna for 5.2 GHz WLANMIMO Application. Issue 3 (3rd April 2023) - Sharma, Vinay; Goel, Ananya; Upadhayay, Madhur Deo; Singh, Atul Vir
ABSTRACT: A rectangular patch antenna with π shaped slot is proposed as a miniaturized antenna element with a gain of 5.83 dB for WLAN (5.2 GHz) application. This compact π shaped slot antenna is used as a radiating element for the design of a 2 × 1 MIMO system for WLAN application. A near field passive parasitic element is used in the proposed MIMO antenna to improve the isolation. The MIMO system has a surface area of 0.29λ 2 with a measured gain of 6 dBi and impedance bandwidth of 110 MHz. The diversity characteristics of MIMO are quantified with envelop correlation coefficient of 0.004, capacity loss of 0.35 bits/s/Hz, mean effective gain ratio (less than 1), mutual coupling around −20 dB, and TARC is −14.5 dB. The measured results are in good agreement with the simulation results and validate the proposed design.